تطبيق برنامج شعبة اللغة العربية في تنمية مهارة الكلام بمعهد الاسلامي والى صانجا للبنات تشوكير جومباثع - Mukarromah, Lailatul (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Speaking skills are the ability to understand ideas and read comprehension accurately. Because speaking is not a simple activity as is currently thought to be done by many people, therefore there must be a special interest in learning Arabic, especially in Islamic boarding schools because it is basically a communication tool.The research questions for this research are: (1) How is the implementation of the Arabic language class program at PPP.Walisongo Cukir Jombang? (2) how to improve the speaking skills of female students at PPP.Walisongo Cukir Jombang? (3) What are the motivations and obstacles to the Arabic language class program at PPP.Walisongo Cukir Jombang? Here, the researcher used the qualitative approach, meaning the descriptive analytical method, and the method of collecting data through direct observation, interviews, and documentation. As for the results of the research presented by the researcher, they are: (1) Arabic speaking skills are an education provided by the Department and attended by all female students in class programs and at school, which is held every Saturday, Sunday and Monday. This education really gives enthusiasm to students. speaking ability. (2) The method of memorizing vocabulary is used first and is immediately practiced every day and sometimes the teacher also shows a video in Arabic and follows it together, then the students practice the update individually, the teacher then signals one of the students to come forward. forward and then read while introducing his friend while listening, which can later be practiced in everyday life. (3) Motivation: What makes them enthusiastic about learning are the male and female lecturers who come from outside the boarding school. Obstacles: that we face when speaking Arabic. Because the environment at PPP Walisongo doesn't only have Arabic language programs but there are English language programs, memorizing the Koran, so we only speak Arabic with friends from the same complex.